2020
DOI: 10.3390/ma13081901
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing and Mechanical Performance of Trifurcated Steel Joints for Architecturally Exposed Steel Structures

Abstract: Additive Manufacturing (AM) technology has unique advantages in producing complex joints in architecturally exposed steel structures. This article focuses on the process of manufacturing and investigating the mechanical properties of a reduced scale model of a trifurcated joint using Selective Laser Melting (SLM) method and mechanical tests, respectively. The orthogonal test method was used to optimize the main AM process parameters. Then the trifurcated steel joint was printed using the optimal process parame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Another study that examined trifurcated 3D printed 316L steel joints using SLM processing showed that maximal discrepancies were < 5%. [23] As specially the printing axes I and II showed the highest deviations, it might be necessary to avoid printing large solid volumes. During the cooling process, the solid specimens may deform due to their weight.…”
Section: Discussionmentioning
confidence: 99%
“…Another study that examined trifurcated 3D printed 316L steel joints using SLM processing showed that maximal discrepancies were < 5%. [23] As specially the printing axes I and II showed the highest deviations, it might be necessary to avoid printing large solid volumes. During the cooling process, the solid specimens may deform due to their weight.…”
Section: Discussionmentioning
confidence: 99%
“…Zhou et al [ 21 ] used additive manufacturing technology to prepare 316L stainless steel standard parts and performed tensile property tests. He et al [ 22 ] studied the 3D modeling and printing of tree-like structure joints and verified the mechanical properties of 3D-printed joints through finite element simulation and experimental study. Combining the two aspects, topology optimization is an effective way to realize the optimal design of joints, and additive manufacturing can quickly manufacture high-precision complex joints.…”
Section: Introductionmentioning
confidence: 99%